2023
DOI: 10.1002/chem.202300730
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Shell and Kernel Modifications of Atomically Precise Pd/Ag Superatomic Nanoclusters

Abstract: The first 8-electron Pd/Ag superatomic alloys with an interstitial hydride [PdHAg 19 (dtp) 12 ] (dtp = S 2 P(O i Pr) 2 À ) 1 and [PdHAg 20 (dtp) 12 ] + 2 are reported. The targeted addition of a single Ag atom to 1 is achieved by the reaction of one equivalent of trifluoroacetic acid, resulting in the formation of 2 in 55 % yield. Further modification of the shell results in the formation of [PdAg 21 (dtp) 12 ] + 3 via an internal redox reaction, with the system retaining an 8-electron superatomic configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(72 citation statements)
references
References 54 publications
5
67
0
Order By: Relevance
“…Treatment of [PdHAg 19 (dtp) 12 ] with CF 3 COOH or HBF 4 triggers an internal redox reaction, yielding another 8-electron alloy [PdHAg 20 (dtp) 12 ] + . 84 Both PdHAg 19 and PdHAg 20 contain a PdH-centred icosahedron Ag 12 , which resembles that of PtH@Ag 12 (Fig. 7).…”
Section: Copper and Silver-based Superatomsmentioning
confidence: 93%
See 3 more Smart Citations
“…Treatment of [PdHAg 19 (dtp) 12 ] with CF 3 COOH or HBF 4 triggers an internal redox reaction, yielding another 8-electron alloy [PdHAg 20 (dtp) 12 ] + . 84 Both PdHAg 19 and PdHAg 20 contain a PdH-centred icosahedron Ag 12 , which resembles that of PtH@Ag 12 (Fig. 7).…”
Section: Copper and Silver-based Superatomsmentioning
confidence: 93%
“…By contrast, the hydrido ligands of other discussed clusters serve as charge-balancing ions solely. As suggested by DFT data, 84 the Pd–H unit of [PdHAg 19 (dtp) 12 ] and [PdHAg 20 (dtp) 12 ] + is formed by interaction of 4d z 2 (Pd) and 1s(H) atomic orbitals to give populated σ(Pd–H) and unpopulated σ*(Pd–H) molecular orbitals. Owing to the strong destabilization of the σ*(Pd–H) orbital, the unpaired electron occupies the 5s(Pd) orbital, thereby contributing to the building of the superatomic orbitals.…”
Section: Copper and Silver-based Superatomsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that interstitial hydrides connected to noble metals, whose electronegativity values are larger than H, exhibit properties that differ from those of conventional ligands. 13,31 Therefore, accurately identifying the hydride position is important, as hydrides may exhibit different properties at different positions. Also, an interesting question is: can an 1a).…”
Section: ■ Introductionmentioning
confidence: 99%